The innovative design of the endcap disc DIRC detector for PANDA at FAIR - Schmidt, M.; Duren, M.; Etzelmüller, E.; Föhl, K.; Hayrapetyan, A.; Köseoglu, I.; Kreutzfeld, K.; Rieke, J.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; et al. (Proceedings of the 2019 Meeting of the Division of Particles and Fields of the American Physical Society, DPF 2019, 2019)
The key component of the future PANDA experiment at FAIR is a fixed-target detector for collisions of antiprotons with a proton target up to a beam momentum of 15 GeV/c and is designed to address a large number of open questions in the hadron physics sector. In order to guarantee an excellent PID for charged hadrons in the polar angle range between 5° and 22°, a new type of Cherenkov detector called Endcap Disc DIRC (EDD) has been developed for the forward endcap of the PANDA target spectrometer. The desired separation power of at least 3 s.d. for the separation of π± and K± up to particle momenta of 4 GeV/c was determined with simulation studies and validated during various testbeam campaigns at CERN and DESY.
CRIS-Team Scopus Importer:2021-04-20